California Bowl Football Game at Bulldog Stadium; Eastern Michigan Hurons 30 v. San Jose Spartans 27 - Watkins, Howard::::::::: (1987)
San Jose State (in blue) scores on 12 yard pass play from Mike Perez to Johnny Johnson